Veil Gripped by Orientalism: State Interference in Islamic Clothing Practices - Kalčić, Špela (Two Homelands, 2011)
State interference in clothing practices, whether in the form of passing a new law, regulations on acceptable ways of dressing in diff erent public institutions or propaganda regarding a certain style of dress have a long tradition in numerous Islamic as well as Western countries. By regulating dress codes, state authorities of the most diverse socio-political backgrounds radically interfere with people’s everyday life and their personal clothing choices, which functions to maintain or establish desired social circumstances. Since time immemorial, women have been at the centre of such clothing regulations. One of the most controversial and by states the most often regulated forms of women’s clothing in the 20th and 21st centuries is without doubt the various forms of veiling among Muslim women.